2020
DOI: 10.3892/ijmm.2020.4521
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin inhibits epithelial‑mesenchymal transition of renal cell carcinoma through autophagy‑dependent Wnt/β‑catenin signaling

Abstract: Silibinin is a flavonoid extracted from milk thistle seeds which has been widely used as a hepatoprotective and antioxidant agent. Recently, accumulating evidence has demonstrated the anti-cancer effects of silibinin in various cancer models. It was previously reported that silibinin induced apoptosis and decreased metastasis by activating autophagy in renal cell carcinoma (RCC). However, the underlying molecular mechanisms by which silibinin regulates autophagy remain largely unknown. The aim of the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…On the other hand, the metastasis-suppressive role of autophagy during the tumor cellular process involves selectively downregulating the key transcription factors or proteins of EMT in the early stage of tumorigenesis [ 105 ]. Autophagy caused by nutritional deprivation or inhibition of related mechanism targets of the mTOR pathway reduces the migration and invasion of glioblastoma cells [ 107 ]. Autophagy and cell motility at the molecular level are regulated by focal adhesion kinase (FAK), FAK interacting protein 200kD (FIP200), and Paxillin (PXN) [ 103 ].…”
Section: Interaction Between Autophagy and Tumor Cell Migration Imentioning
confidence: 99%
“…On the other hand, the metastasis-suppressive role of autophagy during the tumor cellular process involves selectively downregulating the key transcription factors or proteins of EMT in the early stage of tumorigenesis [ 105 ]. Autophagy caused by nutritional deprivation or inhibition of related mechanism targets of the mTOR pathway reduces the migration and invasion of glioblastoma cells [ 107 ]. Autophagy and cell motility at the molecular level are regulated by focal adhesion kinase (FAK), FAK interacting protein 200kD (FIP200), and Paxillin (PXN) [ 103 ].…”
Section: Interaction Between Autophagy and Tumor Cell Migration Imentioning
confidence: 99%
“…5 9 Conversely, induction of autophagy has been shown to restrain the growth and progression of tumor cells in several cancers, including breast cancer, hepatocellular carcinoma and RCC. [10][11][12] In line with this, a study by Li et al 13 showed the anti-metastatic effect of autophagy induction in an adenocarcinoma; renal cell (ACNH) and 786-O RCC cell model-based study. In contrast to the work by Radovanovic and colleagues, this study demonstrated that the AMPK/mTOR pathway was involved in autophagy induction.…”
Section: Dear Editormentioning
confidence: 72%
“…Autophagy can support the energy requirement of cancer cells for growth and metastasis 5 9. Conversely, induction of autophagy has been shown to restrain the growth and progression of tumor cells in several cancers, including breast cancer, hepatocellular carcinoma and RCC 10-12. In line with this, a study by Li et al 13 showed the anti-metastatic effect of autophagy induction in an adenocarcinoma; renal cell (ACNH) and 786-O RCC cell model-based study.…”
mentioning
confidence: 99%
“…Silibinin attenuated the cancer cell metastasis and epithelial to mesenchymal transition through the autophagy-dependent (AMPK/mTOR) downregulation of the Wnt/β-catenin pathway. β-catenin has been previously reported to be degraded through the autophagy-lysosome system, which might have resulted in suppressing the signalling pathway [ 184 , 185 ]. In human colon cancer cells (both primary and metastatic), silibinin treatment activated both extrinsic (TRAIL receptors, caspase-8, 10, Bid) and intrinsic (cytochrome-c, caspase-9) apoptotic pathways associated with induction of cytoprotective autophagy [ 186 ].…”
Section: Roles Of Polyphenols In Autophagic Adaptation For Healthy Agingmentioning
confidence: 99%